The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1478-4491-11-10
|View full text |Cite
|
Sign up to set email alerts
|

Service delivery in Kenyan district hospitals – what can we learn from literature on mid-level managers?

Abstract: BackgroundThere is a growing emphasis on the need to tackle inadequate human resources for health (HRH) as an essential part of strengthening health systems; but the focus is mostly on macro-level issues, such as training, recruitment, skill mix and distribution. Few attempts have been made to understand the capability of health workers, their motivation and other structural and organizational aspects of systems that influence workforce performance. We have examined literature on the roles of mid-level manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…Readiness for change is critical to ensure implementation of the maternity unit activities. Maternity unit activities confronted challenges similar to other studies in Africa, including inadequate knowledge and skills combined with broader health systems failures and low staffing [ 33 , 34 ]. Prior attention to macro issues related to workforce training, recruitment, retention and distribution recently shifted to human resources for health for strengthened health systems [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Readiness for change is critical to ensure implementation of the maternity unit activities. Maternity unit activities confronted challenges similar to other studies in Africa, including inadequate knowledge and skills combined with broader health systems failures and low staffing [ 33 , 34 ]. Prior attention to macro issues related to workforce training, recruitment, retention and distribution recently shifted to human resources for health for strengthened health systems [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior attention to macro issues related to workforce training, recruitment, retention and distribution recently shifted to human resources for health for strengthened health systems [ 35 ]. Focus has turned to health workers capabilities, their motivations and other structural and organizational aspects of systems that influence and moderate workforce performance including leadership and supervision (mid-level management) and communication [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect is the need to involve and communicate clearly with health workers and managers about the policy vision and goals, as well as about what and when actions will be taken [ 25 , 36 ]. It is recognized that leadership, supervision, information dissemination and communication are major mediators and moderators of the quality and effectiveness of health care [ 37 ]. It is also important to increase human resource strength in the facilities in order to address workload issues and improve quality of services that will attract and retain the high number of mothers seeking skilled delivery following the initiation of the program.…”
Section: Discussionmentioning
confidence: 99%
“…HWs' availability had an average score of 53.5%. Similarly, despite the fact that policies are in place to ensure the availability of HWs, less than half of HWs were present in their place of work and active at the time of survey [9,19,20]. Contrary, most respondents interviewed reported that the health providers were available in their place of work and that they were productive [16].…”
Section: Performance Of Health Workersmentioning
confidence: 99%